B+L violation at colliders and new physics - Cerdeño, David G.; Reimitz, Peter (Journal of high energy physics, 2018)
Chiral electroweak anomalies predict baryon (B) and lepton (L) violating fermion interactions, which can be dressed with large numbers of Higgs and gauge bosons. The estimation of the total B + L-violating rate from an initial two-particle state — potentially observable at colliders — has been the subject of an intense discussion, mainly centered on the resummation of boson emission, which is believed to contribute to the cross-section with an exponential function of the energy, yet with an exponent (the “holy-grail” function) which is not fully known in the energy range of interest. In this article we focus instead on the effect of fermions beyond the Standard-Model (SM) in the polynomial contributions to the rate. It is shown that B + L processes involving the new fermions have a polynomial contribution that can be several orders of magnitude greater than in the SM, for high centre-of-mass energies and light enough masses. We also present calculations that hint at a simple dependence of the holy grail function on the heavy fermion masses. Thus, if anomalous B + L violating interactions are ever detected at high-energy colliders, they could be associated with new physics.